Template assisted highly ordered novel self assembly of micro-reservoirs and its replication - Hire, Santosh L.; Shelke, Manjusha V.; Kale, Vinayak S.; Galopin, Elisabeth; Kulkarni, Mohan G.; Boukherroub, Rabah; Ogale, Satishchandra B. (Lab on a Chip, 2010)
A novel method is developed for template assisted fabrication of a regular assembly of microcavity arrays. Simple micropatterns on PDMS mold are used to create complex geometries via solvent vapor back pressure in a biodegradable polymer. Cavities are in turn replicated in complimentary PDMS mushroom like microstructures.